Peer Review and the CQAF : Peer Review as an innovative methodology for external evaluation in VET and its contribution to the further development of the 'Common Quality Assurance Framework'(CQAF) - Gutknecht-Gmeiner, Maria [Verfasser] (My University, 2007)
"The European Peer Review Procedure is based on and supports the principles of the Common Quality Assurance Framework bye providing a new methodology for external evaluation in VET. The European Peer Review procedure enhances transparency and comparability - both regarding the evaluation methodology and the quality areas/indicators used - and fosters European cooperation through transnational evaluations at the Institutional level. The European Peer Review procedure has been developed with the explicit aim to contribute to quality policies on European and national levels. It thus fully corresponds to the central tenets and goals of the 'Common Quality Assurance Framework'. Furthermore, Peer Review is expected to contribute to the CQAF in the following areas: 1) Enriching the methodological repertoire - Peer Review as external evaluation methodology in the CQAF model 2) Implementing the CQAF - Peer Review as a systematic procedure following the criteria of the CQAF model 3) Calling for external perspectives - contribution for Peer Review to external monitoring 4) Learning and teaching in the centre - key topics of a Peer Review 5) Making sense of indicators - qualitative and quantitative indicators in Peer Review 6) Enhancing mutual trust in Europe - transparency, understanding and mutual learning as main aims of Peer Review." (ÖIBF, BIBB-Doku)
Keywords: L 6.2 Qualitätsmanagement/Qualitätssicherung; L 6.2.3 Evaluation; S 1 Stufen der Berufsbildung; Qualitätssicherung; Evaluation; Peer Review; Berufsbildung